Improvement of surface quality using silicon carbide powder added dielectric fluid during EDM - Khan, Ahsan Ali; Mohamad Royani, Nurul Nasuha; Al Hazza, Muataz Hazza Faizi; Che Daud, Mohd Radzi; Mohiuddin, A. K. M. (IOP Publishing, 2017)
In recent years there is an increasing interest of Electrical Discharge Machining (EDM) process, with particular emphasis on the potential of this process for surface modification. In this study, the effect of various EDM parameters on the material removal rate (MRR), tool wear rate (TWR) and surface roughness (SR) using powder-mixed electrical discharge machining (PMEDM) was carried out by using Silicon Carbide (SiC) powder. The workpiece material used was high carbon steel AISI 1050 and the electrode tool material was copper (Cu). Experiments have been designed using full factorial design of experiment (DOE) and the 3 factors were designed for 2 levels. The input process parameters used were the concentration of powder from 0.0 to 5.0g/L, peak current ranging from 2.5A to 4.5A and pulse-on time ranging from 8μs to 10μs. The result shows that when silicon carbide powder is mixed into dielectric fluid during EDM process, it gives minor effect on material removal rate (MRR), but improves tool wear rate (TWR) and surface roughness (Ra). However, as peak current and pulse-on time increase gradually, all responses follow the same trend.